Centralisation of services for gynaecological cancers — A Cochrane systematic review - Woo, Yin Ling; Kyrgiou, M.; Bryant, A.; Everett, T.; Dickinson, H.O. (Elsevier, 2012)
Objective: Gynaecological cancers are the second most common cancers among women. It has been suggested that centralised care improves outcomes but consensus is lacking. This systematic review assesses the effectiveness of centralisation of care for patients with gynaecological cancer, in particular, survival advantage.